Quality Standards for Sample Processing, Transportation, and Storage in Hemostasis Testing - Adcock Funk, Dorothy M.; Lippi, Giuseppe; Favaloro, Emmanuel J. (Seminars in Thrombosis and Hemostasis, 2012)
Samples for hemostasis testing drawn into sodium citrate anticoagulant are vulnerable to the effects of preanalytical variables associated with sample processing, transportation, and storage. These variables include the temperature at which samples are transported and stored; the stability of the samples once processed; whether maintained at room temperature, refrigerated, or frozen; methods of centrifugation; as well as the potential impact of using an automated line. Acknowledgment of these variables, as well as understanding their potential impact on assay results, is imperative to the reporting of high quality and accurate results. This article discusses the preanalytical issues associated with sample processing, transportation, and storage and also presents the ideal conditions for sample handling.
Keywords: preanalytical variability; coagulation testing; prothrombin time; activated partial thromboplastin time; laboratory errors; quality standards